Prolonged Partial REBOA: A Practice Paradigm for Managing Hemorrhage from Abdominal Gunshot Wounds - Zebley, James A; Halpern, Alex I; Matecki, Mary; Napolitano, Michael; Sarin, Shawn; Sarani, Babak (Journal of Endovascular Resuscitation and Trauma Management, 2023)
Resuscitative endovascular balloon occlusion of the aorta (REBOA) is a valuable tool for management of life-threateningtruncal hemorrhage. However, prolonged use of REBOA is limited by the ischemia that it causes distalto the occlusion. Partial REBOA (pREBOA) is a developing technique to inflate the balloon partially to allow for avariable degree of distal blood flow and mitigate some of the complications of prolonged occlusion of the aortawhile also ameliorating ongoing blood loss. We describe a case of a patient who presented with a gunshot woundto the right upper quadrant of the abdomen with significant liver, kidney, and colon injuries. The patient was successfully treated with pREBOA for 20 hours without ischemic sequalae. This is the longest reported use of prolonged pREBOA and suggests that this technique may offer a means for hemorrhage control in the pre-/intra- and postoperative settings.